Effects of Accurate MS Delays on Productivity, Energy Consumption at the Primary Crusher, Oversize, and Ground Vibrations and Airblast - Steven L. Burchell; James W. Reil; Douglas A. Anderson (International Society of Explosives Engineers, 1986)
A total of 26 full-scale production blasts at three sites were extensively monitored with sophisticated instrumentation systems to determine the benefits of more accurate detonators. The new and more accurate MS electric Masterdet detonator was tested against conventional detonators to determine any increase in productivity outputs. All blast design parameters between paired blasts were kept as constant as possible with the only difference being the inherent accuracy of both detonator systems.